Aktivasi Argumentasi Melalui Model Pembelajaran Provokatif-Interaksial dengan Optimalisasi Kecerdasan Buatan ChatGPT pada Kelas Bahasa Indonesia Mahasiswa Universitas Airlangga - Subargo, Yopi Lutfi; Satrio, Prakrisno; Hayani,; Abni, Septia Rizqi Nur (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to improve understanding of Indonesian language material through the provocative-interactional (PPI) learning model by optimizing ChatGPT's artificial intelligence (AI) in searching references during discussions. Research focus: 1) how to optimize ChatGPT in finding references; 2) How to increase the activeness of Airlangga University students in the 2023-2024 Indonesian language class with the support of ChatGPT artificial intelligence in scientific discussions. This type of research is action research with data collection techniques through: document study (literature review), observation, measurement (pretest and post test). The research subjects were Airlangga University students in the first semester, 2023-2024 in Indonesian language teaching classes. The research results show that 1) the arguments in the discussion have references that can be justified through reference tracking using ChatGPT; 2) the discussion process is more active using the PPI model with ChatGPT support.